Green Tourism Branding Strategies to Enhance the Attractiveness of Pematang Johar’s Natural Tourism - Albert Herlambang; Putri Mentari; Sipnarong Kanchanawongpaisan; Muhammad Hafiz Abd.Rashid; Nurul Ilyana Binti Muhd Adnan; Chyntia Agustin (Eastasouth Institute, 2025)
The concept of green tourism has emerged as a strategic approach to promoting sustainable destinations while protecting environmental and cultural resources. This community service program was designed to strengthen the branding and promotion of Pematang Johar Village—an emerging natural tourism destination in Deli Serdang Regency—through green and sustainable tourism strategies. Using a Service-Learning and Participatory Action Research (PAR) framework, the program involved 38 participants, including local tourism managers, MSME owners, and youth volunteers. Activities included workshops on destination branding, eco-friendly tourism practices, and digital marketing for green tourism. The results showed a marked improvement in participants’ understanding of green tourism principles and destination branding, with a 60% increase in awareness and active adoption of eco-friendly initiatives. The creation of a unified slogan and digital campaign “Green Pematang Johar: Where Nature Meets Harmony” helped align local tourism and MSME promotion under a single identity.